Wikileaks: US supported Khmer Rouge to weaken Soviet-allied Vietnamese communists - Norton, Ben (Ben Norton, 2015)
1978 diplomatic cables released by Wikileaks show the US supported the Khmer Rouge to weaken the Vietnamese communists and maintain "stability" in Cambodia